Menentukan Matakuliah yang Efektif Belajar Daring (Belajar dan Ujian) dengan Metode Multi-Attribute Utility Theory (MAUT) - Tonni Limbong; Janner Simarmata (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The Corona pandemic in Indonesia forced the learning system into a drastic change into online learning. Many campuses that were previously quite comfortable with face-to-face learning were forced to be helpless because they had never prepared a backup plan when something unexpected happened, one of which was when the campus was forced to not be able to face-to-face. If the learning system continues to be done online, it might cause the quality of learners to decrease dramatically compared to face-to-face learning. Moreover, the courses that must be filtered include theories and practice courses. Most assignments given to students are not seriously done because of a lack of significant evaluation and supervision. The Faculty of Computer Science, Santo Thomas Catholic University, Medan supports this government policy by implementing online learning using the Zoom application for face-to-face and Edmodo for supplementary lecture material for online learning media. In one semester apart from studying there is a test period which is the Midterm Examination (UTS) and Final Examination Semester (UAS) where the current leadership must wisely determine the type and nature of the exams to be conducted online. To find out the effectiveness of the form of exam questions in online implementation, a Multi-Attribute Utility Theory (MAUT) method was conducted, the test results found that online learning with Zoom and Edmodo was very effective for theoretical courses with a value of 0.88, then the results of this calculation it is recommended that online tests be conducted in the form of theories such as multiple-choice, essay and analysis